2014
DOI: 10.1016/j.virol.2014.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection of primate genes that promote HIV-1 replication

Abstract: Evolutionary analyses have revealed that most host-encoded restriction factors against HIV-1 have experienced virus-driven selection during primate evolution. However, HIV also depends on the function of many human proteins, called host factors, for its replication. It is not clear whether virus-driven selection shapes the evolution of host factor genes to the extent that it is known to shape restriction factor genes. We show that 5 out of 40 HIV host factor genes (13%) analyzed do bear strong signatures of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 69 publications
(114 reference statements)
1
62
0
Order By: Relevance
“…Their circulating levels of free or unbound cortisol are approximately 100 times greater than that found in humans or Old World primates (Klosterman et al, 1986). They are also frequently used in infectious disease, genetics, pharmacology, behavioral pharmacology, drug addiction, and toxicology research (Tardif et al, 2011b;Myers et al, 2007;Brandler et al, 2012;Meyerson et al, 2014;Rowlett et al, 2005;Valdez et al, 2007;Achat-Mendes et al, 2012). They are also frequently used in infectious disease, genetics, pharmacology, behavioral pharmacology, drug addiction, and toxicology research (Tardif et al, 2011b;Myers et al, 2007;Brandler et al, 2012;Meyerson et al, 2014;Rowlett et al, 2005;Valdez et al, 2007;Achat-Mendes et al, 2012).…”
Section: Research Usesmentioning
confidence: 99%
“…Their circulating levels of free or unbound cortisol are approximately 100 times greater than that found in humans or Old World primates (Klosterman et al, 1986). They are also frequently used in infectious disease, genetics, pharmacology, behavioral pharmacology, drug addiction, and toxicology research (Tardif et al, 2011b;Myers et al, 2007;Brandler et al, 2012;Meyerson et al, 2014;Rowlett et al, 2005;Valdez et al, 2007;Achat-Mendes et al, 2012). They are also frequently used in infectious disease, genetics, pharmacology, behavioral pharmacology, drug addiction, and toxicology research (Tardif et al, 2011b;Myers et al, 2007;Brandler et al, 2012;Meyerson et al, 2014;Rowlett et al, 2005;Valdez et al, 2007;Achat-Mendes et al, 2012).…”
Section: Research Usesmentioning
confidence: 99%
“…To assess which primate species should be the focus of our screen, we looked at patterns of evolution in the D1 domain across the primate phylogeny. Currently, CD4 sequences exist for 27 different primate species, 14 of which were generated by our group in a previous study (3). We sequenced CD4 from representative individuals of 4 additional species (Nancy Ma's owl monkey, Aotus nancymaae; Azara's owl monkey, Aotus azarae; Spix's owl monkey, Aotus vociferans; and Bolivian/Peruvian squirrel monkey, Saimiri boliviensis) and used the resulting 31-species CD4 data set to model the pattern of substitutions that has occurred along each branch of the primate phylogeny, using PAML (30) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the T cell receptor interacts with the presented peptide antigen, the D1 domain of CD4 interacts with an invariant portion of the MHC class II molecule itself (1), an interaction that is expected to be preserved over evolutionary time. Despite this, we and others previously demonstrated that CD4 is evolving under diversifying selection in primates, with natural selection working in favor of new allelic forms (2)(3)(4). This is presumably because the CD4 D1 domain also interacts with the envelope (Env) surface protein of the lentiviruses human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) (Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, proteins comprising the immune systems of multicellular eukaryotes are often involved in evolutionary arms races with pathogens, leading to rapid and highly variable evolutionary trajectories [2527]. Proteins directly interacting with pathogen factors are expected to evolve particularly rapidly, and genome-wide comparisons have generally supported this expectation [2830]. No detailed ASR studies have yet been conducted on primary immune receptors, so we have little experimental information about how the evolution of structure-function occurs in these systems, particularly across large evolutionary timescales.…”
Section: Introductionmentioning
confidence: 99%